On Gravitational Fields in Superconductors - Papini, Giorgio (Frontiers in Physics, 2022)
DeWitt's theory on superconductors in gravitational fields is re-derived in the low velocity limit and linear gravity from the Klein-Gordon equation for an ensemble of charged spinless bosons. The solution has a phase singularity that gives rise to boson condensation and enables the description of type-II superconductors in the presence of gravity.